The body mass of Goldcrests Regulus regulus at three closely situated stopover sites during autumn migration in southeastern Sweden - Larsson, Rolf (Ornis Svecica, 2011)
Goldcrests Regulus regulus trapped during autumn migration at three sites in southeastern Sweden (inland, peninsula cape, and island) showed significant differences in mean body mass, about the same in both males and females: 0.71 g heavier inland than on the island, 25 km to the south, and 0.25 g heavier inland than at the peninsula 8 km to the south. The main reason for the difference was that mean body mass decreased during the day at the island and peninsula sites while it increased strongly at the inland site. Data on wind direction during night was compared with the mean body masses the following days at the different sites. The lightest birds were trapped after nights with wind from the east and the heaviest after nights with wind from south to west. It is assumed that these light birds had started off from the eastern side of the Baltic and that this resulted in low body masses after a direct night flight. They then rapidly moved to more favourable inland sites to recover mass.